(untitled) (New Collegium, 2020)
University-School clusters: Best practices and the prospects for their adaptation to Ukrainian context : the XVIII International Scientific and Practical Conference (14-th Febuary 2020, Kharkiv Univ. of Humanities “People’s Ukrainian Acad” The actual value and great importance of the research work organizing in a modern educational institution is considered. The markers of assessment of the effectiveness of research work in the modern educational process are analyzed. The dependence between the educational methods that use research programs and formation of professional competence of graduates, who are demanded on the labor market, is emphasized. The specific features of the research work organization in continuing education complex are characterized. The conclusions are made about the fact of disbalance between the method of organization and supervision of students research work of students in educational complexes «school-university». The necessity of the complex approach to the system of preparing and organizing the research work is stressed. The example of Kharkov University of Humanities «Peoples Ukrainian Academy» is considered, the specific features of research work organizing in the system «school-university» are presented. The forms and systems of organizing the complex training in the sphere of research are given.